(3efXheI aj GdYOOs - (3GdfLaj, , GdCYSe, eMeO Hf Ydj Hf MSjf Hf eMeO, J (B1233(3g`s ((3MSjf Hf eMeO Ydj GdCYSes)
(3ChdgG (B:s
(3dfMeO Gddg eUdjf Ydi (B*** (3fHjG NjQ fHj CQSdGs
(3BNQgG (B:s
(3aEf JHGjfG aaj eKGdg(B***(3JLYd cd YOO HMGdgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B6(3, U(B297s
(3eYLe GdeDdajf(B: (3L(B3(3, U(B484s
(3eYLe GdeDdajf(B: (3L(B3(3, U(B484s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3abg GdePGgH GdCNQis